(untitled) (Global Journal of Science Frontier Research, 2014)
Time shift of the target reflected signal in radar system can be calculated directly from modified QPSK mapped OFDM signal. It makes possible to determine target distance from radar station. When time shift respecting to phase delay depends on OFDM subcarrier number, modified OFDM signal prevents that dependence and lets system to decide the phase delay directly from QPSK-OFDM signal rotation angle of constellation points. Additionally, proposed system requires low computing resources as the entire calculation process could be done during a single OFDM symbol.